Les coulisses de l'État social : enquête sur les signalements d'enfant en danger - Serre, Delphine (Cours et travaux, 2009)
Pour expliquer le contexte et les critères de signalement par les professionnels de l'administration sociale d'affaires d'enfants maltraités, D. Serre a mené des entretiens auprès d'assistantes sociales et les a suivies dans leurs différentes activités. Cette enquête révèle ce que représente la catégories d'enfants en danger et ce que l'acte de signaler signifie pour les professionnels.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; enfance; europe; fem7000; france; inégalités; maltraitance; maternité; protection de l'enfance; régions géographiques; sciences humaines; sciences sociales; services sociaux; systèmes d'oppressions; thématiques; travail social; violences

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Sexe et société : la question du genre en sociologie - Méjias, Jane (Bréal, 2005)
Extrait de l'introduction : "Depuis quelques années, la question des relations entre les hommes et les femmes dans la société est revenue sur le devant de la scène. Plutôt tombée en désuétude dans les années 1980, elle est redevenue une question socialement vive, c'est-à-dire donnant lieu à un vif débat, dans le grand public comme dans le champ scientifique. Dès qu'on l'aborde, elle laisse bien peu de personnes indifférentes."
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; europe; fem1000; france; genre; identités LGBTQIA2+; inégalités; premier cycle; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex3383; sociologie; systèmes d'oppressions; thématiques; travail

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs -- qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those -- the vast majority -- who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe

L'invention de l'hétérosexualité - Katz, Jonathan (Grands classiques de l'érotologie moderne, 2001)
L'auteur retrace l'histoire du concept d'hétérosexualité. Il analyse les textes d'auteurs comme Freud, Richard von Krafft-Ebing, Michel Foucault, Betty Friedan ou Kate Millet. Il nous montre que la distinction homosexuel/hétérosexuel ne repose pas sur une nature immuable mais constitue une façon récente de classer et de juger la société. [SDM].
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; hétérosexualité; identité sexuelle; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex1181; sex1183; sexologie; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; épistémologie

Experiments in knowing: Gender and method in the social sciences - Oakley, Ann (The New Press, 2000)
Ann Oakley came to widespread attention as part of the new school of British feminists to emerge in the 1960s, and has since earned a reputation as one of the most innovative feminist thinkers and social scientists writing today. In Experiments in Knowing, a major new work, Oakley integrates her personal and professional thinking to examine the historical development of methodology in the social and natural sciences, demonstrating how both fields have been subject to a process of "gendering." Oakley not only reconciles the long-standing opposition between the quantitative and the qualitative methods but shows that the experimental and intuitive approaches must be used in tandem to provide a full understanding of any subject of scientific inquiry. Written in accessible language, Experiments in Knowing addresses themes of common interest across such diverse fields as social policy, education, health, and women's studies. Certain to generate considerable debate, it is both a fascinating history of the practice of social science from a feminist perspective, as well as an argument for a new way of thinking about our ways of knowing.
Keywords: 1900-1999; approches et analyses; cours; discipline; europe; fem1000; genre; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sciences sociales; thématiques; théories féministes; épistémologie